The effect of Goods and Services Tax (GST) imposition on stock market overreaction and trading volume in Malaysia and Australia - Lee, Yok Yong; Mohamed Hisham Yahya,; A.N. Bany-Ariffin,; Aslam Izah Selamat, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper investigates the GST imposition effect on stock overreaction and trading volume in Bursa Malaysia and Australian Securities Exchange (ASX). To evaluate the stock overreaction, t-test, Wilcoxon Signed-Rank Test and MannWhitney U-Test are employed to analyse the market-adjusted abnormal returns. The homogeneity of stock trading volume is assessed by block resampling bootstrapping, t-test and regression. Consistent with the Overreaction Hypothesis, this research reveals that all arbitrage portfolios over one-month interval in Bursa Malaysia are able to generate significant abnormal profits. This infers the profitability of implementing short-term contrarian strategy in the Malaysian stock market. However, the analysis for ASX shows the opposite. Additionally, GST imposition reduces the trading volume in Bursa Malaysia but not in ASX. This empirical result will be of interest to the policymakers who are considering imposing tax on fee-based financial services, as well as the investors and fund managers who are concern about profits maximisation.